2018
DOI: 10.3389/fmats.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of the Waste Cigarette Butts for N-Doped Carbon Anode in Lithium Ion Battery

Abstract: As one of the common life garbages, about 4.5 trillion waste cigarette butts are produced and randomly discarded every year due to the addiction to the nicotine and the need of the social intercourse. Such a treatment would result in the waste of the resources and the environmental pollution if they weren't reasonably recycled in time. Herein, the waste cigarette butts were recycled in form of N-doped carbon powders with high economic value-added via one-step facile carbonization at 800 • C for 2 h in the iner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…This biomass was carbonized under a nitrogen atmosphere at 800 C, and used for the fabrication of anodes with good performance. 94 The density at the Fermi level is enhanced by nitrogen atoms behaving as electron donors. Moreover, nitrogen and oxygen atoms within the carbon matrix induce the mechanism of pseudo-capacitive Listorage and the formation of defects, profitable for electrochemical activities.…”
Section: Biowastementioning
confidence: 99%
See 1 more Smart Citation
“…This biomass was carbonized under a nitrogen atmosphere at 800 C, and used for the fabrication of anodes with good performance. 94 The density at the Fermi level is enhanced by nitrogen atoms behaving as electron donors. Moreover, nitrogen and oxygen atoms within the carbon matrix induce the mechanism of pseudo-capacitive Listorage and the formation of defects, profitable for electrochemical activities.…”
Section: Biowastementioning
confidence: 99%
“…Cigarette butt waste is another potential source of biomass containing a high amount of cellulose. This biomass was carbonized under a nitrogen atmosphere at 800°C, and used for the fabrication of anodes with good performance 94 . The density at the Fermi level is enhanced by nitrogen atoms behaving as electron donors.…”
Section: Green Materials Used For the Fabrication Of Lib Componentsmentioning
confidence: 99%
“…Apart from biomass, industrial wastes have also been utilized as electrodes for LiBs. For example, Yu et al [ 127 ] carbonized waste cigarette butts at 800 °C in nitrogen atmosphere, as shown in Figure 13 a. The presence of nitrogen‐containing compounds such as nicotine and hydrogen cyanide in the chemical structure of cigarettes makes it a promising waste resource for the fabrication of N‐doped carbon electrodes for energy storage.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…The cycling performances of N-doped carbon anode at b) 25 mA g À1, c) 1000 mA g À1 , and d) 2000 mA g À1 . Reproduced with permission [127]. Copyright 2018, Frontiers.…”
mentioning
confidence: 99%
“…Accordingly, methods for recycling tobacco waste have been proposed. Reports have also been published regarding recycling CBs into high value materials such as cellulose pulp [2] and N-doped carbon powder [3].…”
Section: Introductionmentioning
confidence: 99%